Extracranial germ cell tumours in children and adolescents: Results from the French TGM13 protocol. Issue 3 (30th November 2022) - Faure‐Conter, Cecile; Orbach, Daniel; Sudour‐Bonnange, Hélène; Verité, Cecile; Mansuy, Ludovic; Rome, Angelique; Dumesnil, Cecile; Thebaud, Estelle; Renard, Marleen; Hameury, Frederic; Flechon, Aude; Blanc, Ellen; et al.
Abstract: Background: Chemotherapy for non‐seminomatous germ cell tumours (NSGCT) exposes to dose‐dependent toxicities. The TGM13‐NS protocol (EudraCT 2013‐004039‐60) aimed to decrease the chemotherapy burden compared to the previous TGM95 protocol while maintaining the 5‐year event‐free survival (EFS) at 80% or more. Procedure: Patients less than 19 years of age with disseminated NSGCT were enrolled (May 2014 to May 2019) and stratified into four groups: two intermediate‐risk (IR: localised tumour with low tumour markers [TM]) groups treated with VBP (vinblastine–bleomycin–cisplatin): three courses for IR1 (ovarian tumour any age/testis tumour less than or equal to 10 years) and four courses for IR2 (extragonadal tumour 10 years or less) groups, and two high‐risk (HR: metastatic and/or high TM) groups treated with etoposide–cisplatin and either ifosfamide (VIP) or bleomycin (BEP): three courses for HR1 (ovarian tumour any age/testis tumour less than or equal to 10 years and low TM/testis tumour more than 10 years and very low TM) groups and four courses for HR2 (remainder) groups. Results: One hundred fifteen patients were included: median age of 12.8 years (0.4–18.9); tumour sites: 44 ovaries, 37 testes and 34 extragonadal. The 5‐year EFS and overall survival (OS) were 87% (95% CI: 80–92) and 95% (89–98), respectively (median follow‐up: 3.5 years, range: 0.2–5.9), similar to those of the TGM95 protocol (5‐year EFS 89% (84–93), 5‐year OS 93% (89–95), p  = .561). The 5‐year EFS were 93% (95% CI: 80–98), 88% (71–95) and 79% (62–90) for ovarian, testicular and extragonadal tumours, respectively. The 5‐year EFS varied ( p  = .02) according to the risk groups: 90% (66–97), 64% (30–85), 95% (72–99) and 87% (74–94) for IR1, IR2, HR1 and HR2, respectively. TM decline adjusted to tumour site, and alpha‐fetoprotein (AFP) level revealed a prognostic impact of time to normalisation on EFS: HR = 1.03 (1.003–1.007). Conclusion: Risk‐adapted and globally decreased chemotherapy burden maintains excellent outcomes, exclusive of the IR2 group, which warrants more intensive chemotherapy.